Pengembangan Ant Algorithm Dengan Hybridization Concept Untuk Clustering Data - Bukhori, Saiful (JIK: Jurnal Ilmu Komputer, 2006)
Application of ant algorithm for the problem solving with artificial intelligence has grew at full speed. This problem was related to the behavior of ant that was aimed at strove for sustain the ant colony life. Base on the literature survey, the research that was apply the ant algorithm in data mining scope for clustering data has not done . In this research, researcher was design and analysis application of ant algorithm for clustering data . The algorithm, that was used, was modification and improvement for the algorithm that has developed previously. Ant algorithm that was designed was not used four main parameters, ant desirability, ant frequency, heuristic information (a) and pheromone concentration (b), that used in the previous research[2]. The Software that was designed and implemented in operating system Windows has experimented with data from many sources. The result of the experiment was the true classification in 93,48% - 97,00% range, the false classification in 3,00% - 6,52% range and unclassified 0%. Keyword: data mining, clustering data, ant algorithm, hibridization concept